ROMANIAN DEFENSE RESOURCES MANAGEMENT UNDER CRISIS CONDITIONS - Iulian N. BUJOREANU (Journal of Defense Resources Management, 2010)
Defense resources management is a harder field to deal with in economic and social crisis conditions. It is not under war but peace conditions and one has to understand it as if it were under war conditions. The paper introduces the reader to the possible type of approach and factors to be considered when developing strategies and implementing directives in time of peace with a consideration of resources as if it war in time of war. Risk analysis is of outmost importance in dealing with resource allocation in time of crisis, and directions to it are proposed here. Also, a different view of the chain of command in the hierarchy and its role in crisis time, responsibilities and attributes one should fulfill in the decision-making process for the reason of efficiency and effectiveness in the military field. Finally, a round-up conclusion brings us to the question if anything can be done without the political factor involved and which type of involvement it should be.